"NATURAL HISTORY, PORCELAIN, AND 'MAPPING' EMPIRE AT ARANJUEZ". - ZANARDI, TARA (Dieciocho: Hispanic Enlightenment)
Charles III's office at the Royal Seat of Aranjuez is a tour-de-force of porcelain engineering. The avian, bestial, figural, decorative, and botanical motifs suggest themes of natural history and commerce. The design highlights objects and specimens that voyaged throughout the network of global trade in which Spain participated in a room where domestic and foreign policies were shaped. Considering the room's political purpose and the estate's emphasis on botanical, agricultural, and zoological cultivation, I address the ideological relationship between the porcelain office's depiction of imperial abundance and the agrarian innovations, breeding, and collecting that occurred at Aranjuez.